Proposed sub‐synchronous resonance damping controller for large‐scale wind farms - Zahra Moradi‐Shahrbabak (IET Renewable Power Generation)
Abstract This paper deals with the mitigation of sub‐synchronous resonance (SSR) in doubly‐fed induction generator (DFIG)‐based wind farms using a sub‐synchronous resonance damping controller (SSRDC). The performance of the SSRDC depends on its input control signal and the location of its output control signals. Hence, this paper presents an algorithm to select the best location for applying the SSRDC. The DFIG parameters are used as the inputs of this algorithm. Also, the participation factors analysis is employed as this algorithm's main core. The output of this algorithm determines that the control signal of SSRDC can be applied either in the grid‐side converter (GSC) and/or in the rotor‐side converter (RSC). The best input location in the GSC is the DC‐link voltage and the best input location in the RSC is the q‐component of the rotor voltage. The accuracy of this algorithm was evaluated by investigating the effect of various input signal locations on the SSR using the eigenvalue analysis. This analysis indicated that the dc‐link voltage and the q‐components of the rotor voltage are the most effective signals on the sub‐synchronous oscillatory modes. Moreover, this paper introduces a new SSRDC using these two signals. The performance of this controller is validated through the eigenvalue analysis and a time domain simulation.